Are there sufficient diagnostic criteria for bronchial atypical carcinoid? A case report of bronchial pigmented spindle cell carcinoid with a review of the literature - Lewitowicz, Piotr; Horecka-Lewitowicz, Agata A. (Medical Studies/Studia Medyczne, 2014)
Here we present a case of a 42-year-old female patient with pigmented spindle cell variant of bronchial carcinoid. The aim of this study was not only to record a rare variant of this tumour but also to highlight the differences in diagnostic criteria of gastrointestinal and bronchopulmonary-thymic neuroendocrine neoplasms. Ki-67 index is a discriminating factor in differential diagnosis between gastrointestinal neuroendocrine tumours (NETs) and, only optionally, in bronchopulmonary-thymic tumours. Since diagnosis is currently based on mitotic activity, optionally Ki-67 index and tumour necrosis, a rare variant of NET, spindle cell carcinoids with cellular atypia could be potential pitfalls for diagnostic controversies or mistakes. Nevertheless, the presented case of typical carcinoid with spindle cell component and mild to moderate cellular atypia has been classified according current WHO criteria as a typical carcinoid.